Ion Transport Through Polyelectrolyte Multilayers. Issue 23 (13th November 2013) - Carregal‐Romero, Susana; Rinklin, Philipp; Schulze, Susanne; Schäfer, Martin; Ott, Andrea; Hühn, Dominik; Yu, Xiang; Wolfrum, Bernhard; Weitzel, Karl‐Michael; Parak, Wolfgang J.
<x xml:space="preserve">Abstract</x> Polyelectrolyte multilayer (PEM) films and capsules loaded with ion‐sensitive fluorophores can be used as ion‐sensors for many applications including measurements of intracellular ion concentration. Previous studies have shown the influence of the PEM films/shells on the specific response of encapsulated ion‐sensitive fluorophores. PEM shells are considered as semipermeable barriers between the environment and the encapsulated fluorophores. Parameters such as the time response of the encapsulated sensor can be affected by the porosity and charge of the PEM shell. In this study, the time response of an encapsulated pH‐sensitive fluorophore towards pH changes in the surrounding environment is investigated. Furthermore, the conductance of PEM films for potassium ions is determined. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>